KAUKUS LINGKUNGAN DPRD DALAM MEMPERJUANGKAN KEPENTINGAN LINGKUNGAN DAN MENCAPAI AGENDA POLITIK - I Wayan Suarna (Environmental Research Center (PPLH) of Udayana University, 2008)
Efforts made to achieve clean and healty environment should not merely put on the responsility of executive institutions only, but also all stakeholders who have concerned on environment including house of representatives. The Environmental Caucus of the house representative are expected to improve survailance, budgetting, as well as release of pro-environment regulations which are predominantly related to environmental management. On carrying out sustainable development, providing main attention on environment on any decisions and regulations made is a must. Therefore the existence of Environmental Caucus of the house representative is important because the institution can push any parties to make decission which are pro to the environment on the parliament levels. If we look at the challenge and chance faced by the Environmental Caucus of the house representative, strong commitment needed by their members to fight for pro-environment supporters and take environmental problems as priority on their political agenda.